2011
DOI: 10.1007/s11434-011-4493-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling spatial and temporal variations in soil moisture in China

Abstract: On the basis of station observations, an atmospheric field (ObsFC) was constructed for the Community Land Model version 3.5 (CLM3.5). The model (CLM3.5 driven with ObsFC, hereafter referred as to CLM3.5/ObsFC) was used to simulate soil moisture (SM) from 1951 to 2008 in China. The resulting SM was compared with in situ observations, remote-sensing data and estimations made by various land models, indicating that CLM3.5/ObsFC is capable of reproducing the temporospatial characteristics and long-term variation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 45 publications
10
33
0
Order By: Relevance
“…The above validation indicated that the ensemble soil moisture well reproduced the spatial distribution and linear trends, which can be further used to research regional climate change. Figure 3 shows the spatial distributions of soil moisture and their variances for scenario 20C3M for 1900-1999 and A1B for 2001-2099, which are generally in agreement with the historical simulations for the period of 1951-2008 [22] and which also both agree well with the distributions based on precipitation and temperature [60,61]. The soil moisture decreased gradually from southeast to northwest China, exhibiting high values in the northeast and middle and lower reaches of the Yangtze River.…”
Section: Comparisons Of Ensemble Soil Moisture and Clm35/ Obsfcsupporting
confidence: 79%
See 2 more Smart Citations
“…The above validation indicated that the ensemble soil moisture well reproduced the spatial distribution and linear trends, which can be further used to research regional climate change. Figure 3 shows the spatial distributions of soil moisture and their variances for scenario 20C3M for 1900-1999 and A1B for 2001-2099, which are generally in agreement with the historical simulations for the period of 1951-2008 [22] and which also both agree well with the distributions based on precipitation and temperature [60,61]. The soil moisture decreased gradually from southeast to northwest China, exhibiting high values in the northeast and middle and lower reaches of the Yangtze River.…”
Section: Comparisons Of Ensemble Soil Moisture and Clm35/ Obsfcsupporting
confidence: 79%
“…Therefore, the monthly series of the ensemble soil moisture cannot be evaluated by using observations. Considering the fidelity of the spatial-temporal variations of the CLM3.5/ ObsFC soil moisture compared to the observations on various time scales (for example, the correlation coefficient is 0.84 for CLM3.5/ObsFC and observations in northeast China for 1990-2000, showing decreasing trends) [22], Figure 6 shows a comparison of the CLM3.5/ObsFC results and the ensemble soil moisture series, indicating that the variations agree well with each other on the decadal scale, especially over the latter 20 years. The results suggest that this is a practical approach for analyzing the dry-wet conditions and boundary dynamics of climate zones on a decadal scale.…”
Section: Spatial Patterns Of Linear Trends For Ensemble Soil Moisturementioning
confidence: 99%
See 1 more Smart Citation
“…However, the soil moisture variability remains low compared with observations (Lawrence et al 2011). Based on our assessment of the applicability of CLM 3.5 across China and the observation-based datasets (Li and Ma 2010;Li et al 2011), we opted for CLM 3.5 to regenerate the long-term runoff variability. For a detailed description of CLM 3.5, the readers are referred to Oleson et al (2004) and the references therein.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Li et al [32] simulated SM from 1951 to 2008 using station observations and constructed an atmospheric field (ObsFC) for the Community Land Model version 3.5 (CLM3.5). CLM 3.5 is an improved and updated version of community land module derived from the Common Land Model and the Land Surface Model (LSM) of the National Center for Atmospheric Research.…”
Section: Information Processing Technologies For Dementioning
confidence: 99%